Strategies for Development of a Next-Generation Protein Sequencing Platform. Issue 1 (January 2020) - Callahan, Nicholas; Tullman, Jennifer; Kelman, Zvi; Marino, John
Abstract : Proteomic analysis can be a critical bottleneck in cellular characterization. The current paradigm relies primarily on mass spectrometry of peptides and affinity reagents (i.e., antibodies), both of which require a priori knowledge of the sample. An unbiased protein sequencing method, with a dynamic range that covers the full range of protein concentrations in proteomes, would revolutionize the field of proteomics, allowing a more facile characterization of novel gene products and subcellular complexes. To this end, several new platforms based on single-molecule protein-sequencing approaches have been proposed. This review summarizes four of these approaches, highlighting advantages, limitations, and challenges for each method towards advancing as a core technology for next-generation protein sequencing. Highlights: Advancements in high-throughput technologies has enabled rapid and parallel sequencing of genomes and transcriptomes. High-resolution sequencing of attomolar amounts of protein would revolutionize characterization of gene products (the proteome) and subcellular structures. Advancements in nanopore sensors and single-molecule fluorescence methods can now detect specific residues on a peptide, but not yet all 20. Controlling peptide location and orientation is a major technical hurdle in the development of next-generation protein-sequencing modalities. Present work in next-generation protein sequencing suggests future compatibility with multiplexing and microfluidic sampling.